Practices and perspectives in cardiopulmonary resuscitation attempts and the use of Do Not Attempt Resuscitation orders: A cross-sectional survey in Sri Lanka. - Beane, A; Ambepitiyawaduge, P; Thilakasiri, K; Stephens, T; Padeniya, A; Athapattu, P; Mahipala, P; Sigera, P; Dondorp, A; Haniffa, R (Medknow Publications, 2017)
Objective The objective of this study is to describe the characteristics of in‑hospital cardiopulmonary resuscitation (CPR) attempts, theperspectives of junior doctors involved in those attempts and the use of do not attempt resuscitation (DNAR) orders. Methods A cross‑sectional telephone survey aimed at intern doctors working in all medical/surgical wards in government hospitals. Interns were interviewed based on the above objective. Results A total of 42 CPR attempts from 82 hospitals (338 wards) were reported, 3 of which were excluded as the participating doctor was unavailable for interview. 16 (4.7%) wards had at least 1 patient with an informal DNAR order. 42 deaths were reported. 8 deaths occurred without a known resuscitation attempt, of which 6 occurred on wards with an informal DNAR order in place. 39 resuscitations were attempted. Survival at 24 h was 2 (5.1%). In 5 (13%) attempts, CPR was the only intervention reported. On 25 (64%) occasions, doctors were “not at all” or “only a little bit surprised” by the arrest. Conclusions CPR attempts before death in hospitals across Sri Lanka is prevalent. DNAR use remains uncommon.